Input-output techniques : Proceedings of the fifth international conference on input-output techniques, Geneva, January, 1971 (Amsterdam : North-Holland publishing company, 1972)
This is a volume of papers selected from those presented at the Fifth International Conference on Input-Output Techniques in Geneva in January 1971. The Conference was sponsored by United Nations and Harvard Economic Research Project under a grant from the Battelle Memorial Institute.
Sole distributors for the U.S.A. and Canada: American Elsevier Pub. Co., New York.
Including bibliographical references
osa 02/01/19
Loans
Keywords: Brody, A; Carter, A.P.; Input-output analysis; Economics -mathematical model